A New Audio Steganography System Based on Auto-Key Generator - Inas Jawad Kadhim (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
Stenography is the art of hiding the very presence of communication by embedding secret message into innocuous looking cover document, such as digital image, videos, sound files, and other computer files that contain perceptually irrelevant or redundant information as covers or carriers to hide secret messages.